PERBANDINGAN PELAKSANAAN KONSELING KELUARGA TERHADAP PERBAIKAN PERAN KELUARGA DALAM PENGELOLAAN PASIEN PASIEN DM - Benny Siringo ringo; Anna Ester (Journal of Innovation Research and Knowledge, 2022)
BackgroundI f diabetes mellitus is not handled better it will result the complication of the various body organ like eyes, kidney, heart, venous of feet, nerve, etc. The best experience is cooperation between patient, family and health officer, expected chronic complication can be prevented. The aim of this research is to study and prove the influence of family counseling to repair of family role in management of family member with DM. Methods: The research is done in Puskesmas Tukka I on September – November 2019, the population is 29, by using total sampling technique, and there are many people who do not fulfill the criterion of inclusive and exclusive is finally gotten 26 sample family which one of them get it DM. Result: Result of the research is there is significant influence with the average difference 12.97 about family counseling to repair of family role in management of family member with DM in region work of Puskesmas Tukka I in 2019.